Parent-child relationship and smartphone addiction in adolescents: Are there gender differences? - Suprapto, Maria Helena; -, Setiasih; Siaputra, Ide Bagus (Psychological Research on Urban Society, 2023)
This study aims to reveal whether there are differences in father-child relationships and mother-child relationships based on gender and to determine whether the father-child and mother-child relationship affects smartphone addiction in adolescents. This research used quantitative methods. The research participants were 159 male and 229 female adolescents aged 10-15 years in Surabaya and Sidoarjo. Research data was obtained using a questionnaire distributed online (google forms). The data were processed by using a t-test and multiple regression analysis. This research concludes that the quality of the father-child and mother-child relationship does not differ across gender. Father-child relationships and mother-child relationships both affect teenagers' smartphone addiction. The implication of this study emphasizes the importance of parents forming positive quality parent-child relationships by being friends with children, communicating intimately, and reducing parent-child conflicts. Further research is recommended to examine parent-child relationships from two perspectives: parents and adolescents or conduct qualitative research to describe the dynamics of parent-child relationships and smartphone addiction in adolescents. Keywords: Parent-child relationship, smartphone addiction, gender, adolescent